Reliability Study of the Liquid Target Chamber for 18F Production at the BATAN’s Cyclotron Facilities - I. Kambali; T. Heryanto; Rajiman Rajiman; S. Ichwan (PPIKSN-BATAN, 2011)
The liquid target chamber for 18F production at the Cyclotron Division, Centre for Radioisotopes and Radiopharmaceuticals (PRR) of the National Nuclear Energy Agency of Indonesia (BATAN) has been analysed for its reliability in enduring high pressures and heat transfer requirements during proton beam bombardment as well as the recommended irradiation parameters for effective 18F production. The target chamber was subject to house the 18O-enriched water bombarded with high energy proton beam to produce 18F. A range of SRIM-computer simulations have also been conducted to calculate the ranges of several energetic proton beams (of up to 20 MeV) into pure water target. A study of radioactive impurities which might be produced from the proton-irradiated chamber’s materials was also included based on some references. Due to concern over the heat produced during target irradiation, a heat transfer analysis - particularly for the target’s cavity - was also included in the presented studies to obtain a brief preliminary calculation of the heating impacts prior to irradiation tests. The calculation was performed for various proton beam currents and energies of up to 30 μA and 20 MeV respectively. It was found that the chamber was reliable for production of 18F from proton irradiated-18O enriched-water target by maintaining the chamber’s pressure of up to 3.6 bar if the proton beam current was kept below 16 μA for all energies or the proton beam energy was kept to or below 10 MeV for any employed beam currents. The overall heat transfer coefficient was also found to depend on the power deposited into the water target. Received: 25 June 2010; Revised: 20 March 2011; Accepted: 08 April 2011